A new model for Auckland commercial property yields. Issue 1 (4th February 2019) - Szweizer, Moshe
Abstract : Purpose: The purpose of this paper is to extend the studies of commercial property yields by providing a cross-field approach through the implementation of methods used in physics. Design/methodology/approach: Based on the equations used to describe real gases in physics, the commercial property yields are expressed through a model, as a product of two terms. The first term estimates the influence of the income change and investment on yields. The second estimates the yield variation as a function of property size. Additionally, the model combines the macroeconomic and microeconomic components influencing yield adjustment. Calculation of each component involves procedures developed in physics, with the investment volume being linked to the amount of gas and the microeconomic yield being linked to the gas compressibility. Findings: The model was applied to the Auckland office and industrial markets, both to the historic and current cycle. At the macro-level, it was found that the use of accumulation of investment over a relevant cycle, results in a high data to model correlation. When modelling the yields at the micro-level, a relationship between the outlying properties and the yield softening was observed. Practical implications: The paper provides an enhanced modelling power through association of the cyclic and investment activity with the yield change. Moreover, the model may be used to decouple the local and the international investment components and the extent of their influence on the local property market. Furthermore, it may be used to estimate the influence of the property size on the yield. Originality/value: This research provides a new cross-field application of modelling techniques and enhances the understanding of factors influencing yield adjustments.